DESIGN AND DEVELOPMENT OF NOVEL FLOOD DETECTION SYSTEM USING IOT - BODEPUDI MAHESH CHANDRA CHOWDARY, MANNAVA MOHAN SASANK, PREMKUMAR CHITHALURU, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Devastating floods have emerged as a problem for urban planners and decision-makers in recent years due to an increasing frequency of unprecedented rainfall events all over the world. Flood is a Hazardous phenomenon by which world is encountering from several years. Flooding is a natural calamity that is drawing attention from all around the world due to its detrimental effects on civilization. Because flood events change unlikely, efforts must be done to lessen their impact. Dams are very important, because they are especially used to provide hydroelectricity and for irrigation. As a result, numerous dams have been built in possible locations over the years. Due to the numerous danger considerations connected to the presence of such dams, it has become imperative to create an effective monitoring and management system for the opening of the shutters, hence ensuring a safe water level in dams. Dam management errors can result in man-made calamities. Water levels can alter because of abrupt changes in the levels of nearby lakes or rivers that are connected to it, or because of an abundance of rain in catchment area. Hence in this work, design and implementation of novel flood detection using IoT (Internet of Things) is presented. In this work, GSM module (Global System for Mobile communication) and Thing speak platforms are used to alert the people during floods. This system can effectively detect the flood and loss of lives and property damages can be reduced.